Police crime: investigating insider fraud in UK policing - Kassem, Rasha (Deviant behavior, 2024)
This study is the first to provide a holistic view of an understudied topic, insider fraud in UK policing. Using semi-structured interviews with twenty-six UK police officers, it explores insider fraud forms, methods, perpetrators, consequences, and detection. The study finds corruption and asset misappropriation the primary forms of insider fraud in UK policing. Various methods for committing these two fraud schemes are identified. However, abusing authority for sexual gain is the most common form of corruption. In contrast, selling confidential data on police systems to criminals for financial gain is the predominant form of asset misappropriation. Financially motivated insider fraud is less likely to be committed by senior management. Conflicts of interest are more likely to be perpetrated by higher managerial ranks, such as superintendents and above. In most cases, the perpetrators were dismissed rather than prosecuted, and in other cases, they did not even get dismissed. Detecting insider fraud in UK policing is reactive rather than proactive. The findings have implications for policing research, policy, and practice, later discussed.